Effect of Decontamination Treatments on Micro-Shear Bond Strength between Blood–Saliva-Contaminated Post-Etched Dentin Substrate and Composite Resin - Haralur, Satheesh B. (Healthcare (Basel), 2019)
Blood–saliva contamination negatively affects the bonding potential of adhesive agents. The study aimed to assess the effect of various cleaning protocols on micro-shear bond strength (μSBS) between blood–saliva-contaminated post-etched dentin and composite resin in total-etch and self-etch adhesives. The cleaning methods tested were water rinsing, 37.5% phosphoric acid (H3PO4) re-etching, 6% sodium hypochlorite (NaoCl), 2% chlorhexidine gluconate (CXG), isopropyl alcohol (IPA), and pumice. Nono-hybrid composite cylinders with a 3-mm diameter and 2-mm height were directly cured over the dentin substrate, stored for 24 h, and subjected to 12,000 thermocycles. The shear force was exerted with a 200-μm knife-edged chisel-shaped head from a universal testing machine. The type of failure was assessed with stereomicroscope magnified images. The obtained data were evaluated by Kruskal–Wallis and Mann–Whitney U post-hoc tests. Water-rinsed contaminated dentin surfaces showed substantially reduced μSBS in the total etch from 25.93 to 20.29 Mpa and the corresponding values for the one-step self-etch adhesive were 10.10 to 8.8. Re-etching with 37.5% H3Po4 resulted in a recovery of bonding potential in both total-etch (24.58 Mpa) and self-etch adhesive (9.23 Mpa). Alternately, NaoCl and pumice cleaning showed promising results for the total-etch (23.51 Mpa) and self-etch (7.79 Mpa).